PERANCANGAN APLIKASI CUSTOMER RELATIONSHIP MANAGEMENT KLINIK BERBASIS WEB - Wijaya, Avid; Akbar, Prima Soultoni; Sangkot, Hartaty Sarma (P3M Politeknik Negeri Banjarmasin, 2023)
The key to an agency's success lies not only in the quality of its products or services, but also in how much effort a company has to put in to meet customer needs, and then provide them with the best and most comfortable service so they can become loyal customers. Customer Relationship Management (CRM) can not only guarantee customer loyalty to a product, but also loyalty to these companies and agencies in providing health services at a clinic. Implementation of CRM strategy aims to attract new customers, improve customer relationships and retain customers, so as to obtain long-term customer loyalty. This research develops an E-CRM software application, using the action research method. The stages carried out in action research are diagnosing, planning action, taking action, evaluating action. The results of this study are web-based clinical customer relationship management application designs developed with PHP and MySQL programming. This application displays information related to clinical services and facilities that can be accessed by users. Contacts and social media links make it easier for users to stay in touch with the clinic to ask for the information they need. The customer relationship management application in the branding strategy helps in introducing the clinic through web media. Long-term relationships between patients and clinics will be maintained through an informative application system.